Dataset of cell viability and analytes released by cancer cell lines exposed to low pH and conditioned medium - Catherine M. Worsley; Rob B. Veale; Elizabeth S. Mayne (Data in Brief, 2024)
Cancer cells influence their microenvironment by secreting factors that promote tumour growth and survival while evading immune-mediated destruction. We previously determined the expression of secreted factors in breast and oesophageal squamous cell carcinoma cell lines (MCF-7 and WHCO6, respectively) using Luminex assays. These cells were subsequently treated with low pH medium to mimic in vivo acid exposure, and the effects on cell viability, proliferation, and secretion of cytokines, chemokines and growth factors were described [1]. Here, we present the datasets from these experiments in addition to data obtained from treating cell lines with conditioned medium from apoptotic cell cultures.